The Relationship Between Low Testosterone Levels and Asthenia in Adult Patients: An Original Study - Iftikhar, Mehwash; Khan, Imran; Jamal, Ayesha; Khan, Shiraz Jamal (Journal of Postgraduate Medical Institute, 2024)
Objectives: This study assesses the correlation between testosterone levels and fatigue severity, as measured by the NRS. Methodology: This cross-sectional study was conducted from January to July 2024 at Hayatabad Medical Complex, Peshawar. A total of 150 adult patients presenting with asthenia were included. Serum testosterone levels were measured using standardized immunoassays. Fatigue severity was quantified using the Numeric rating scale (NRS), where patients rated their Fatigue on a scale from 0 (no fatigue) to 10 (extremely fatigued). Demographic data was summarized using descriptive statistics, while the Pearson correlation coefficient (r) was employed to evaluate the relationship between testosterone levels and fatigue severity. Results: The frequency of low testosterone levels (<300 ng/dL) in the study was 40% (n=60). The average testosterone level for the low testosterone group was 250 ± 20 ng/dL, compared to 450 ± 30 ng/dL for those with normal testosterone levels. Patients with low testosterone had significantly higher Fatigue NRS scores (7.5 ± 1.5) than those with normal testosterone levels (3.2 ± 1.1) (p < 0.001). A significant negative correlation was observed between testosterone levels and fatigue NRS scores (r = -0.65, p < 0.001). Conclusion: Low testosterone levels are prevalent in adult patients with asthenia and are significantly associated with increased fatigue severity, as measured by the NRS. These findings suggest that assessing testosterone levels in patients presenting with unexplained asthenia may be valuable, and testosterone replacement therapy could offer potential therapeutic benefits.